High altitude modulates concussion incidence, severity, and recovery in young athletes. (12th May 2022) - Li, Adam Y.; Durbin, John R; Hannah, Theodore C; Ali, Muhammad; Spiera, Zachary; Marayati, Naoum Fares; Dreher, Nickolas; Schupper, Alexander J.; Kuohn, Lindsey; Gometz, Alex; Lovell, Mark R.; Choudhri, Tanvir F.
ABSTRACT: Background: High altitude may affect concussion, but prior studies are limited . We tested whether high altitude affects sport-related concussion (SRC) incidence, severity, and recovery. Methods: Twenty-five thousand eight hundred fifteen baseline and post-injury Immediate Post-Concussion Assessment and Cognitive Testing results were compiled from Florida and Colorado, low (27 m or 62 m) and high (1, 640 m or 1, 991 m) altitude locations, respectively. Incidence, severity, and recovery of injury were compared between altitudes. Results: High altitude was associated with increased suspected concussion incidence (adjusted OR, 2.04 [95% CI, 1.86 to 2.24]; P < .0001). However, high altitude was associated with lower concussion severity measured by Severity Index (SI) (adjusted OR, 0.42 [95% CI, 0.37 to 0.49]; P < .0001). High altitude was associated with decreased recovery from post-concussive symptoms in the migraine (β, −2.72 [95% CI, −3.31 to −2.13]; P < .0001), cognitive (β, −1.88 [95% CI, −2.40 to −1.36]; P < .0001), and sleep symptom clusters (β, −0.30 [95% CI, −0.52 to −0.08]; P = .007). Athletes with initial SI≥8 showed prolonged neurocognitive dysfunction at high altitude (HR, 1.38 [95% CI, 1.06 to 1.81]; P = .02). Conclusions: High altitude was associated with increased suspected concussions and prolonged recovery but less severe initial injury.